High Prevalence of Pfhrp2/3 Gene Deletions and Major Threat to Malaria Control Programs in Ethiopia - Sisay Getie; Gebeyaw Getnet Mekonnen; Aline Lamien Meda; Meseret Birhanie; Aberham Abere; Harald Noedl (Journal of Tropical Medicine)
Conclusions: Our study provides widespread deletions in the Pfhrp2 and Pfhrp3 genes in Ethiopia, thereby confirming anecdotal reports of diagnostic failure with Pfhrp2-based RDTs in the region. The implications of our finding for the current diagnostic paradigm, which relies on the detection of P. falciparum by Pfhrp2-based RDTs in remote areas, may need rethinking.